Review paperOral retinoids and rexinoids in cutaneous T-cell lymphomas - Sokołowska-Wojdyło, Małgorzata; Ługowska-Umer, Hanna; Maciejewska-Radomska, Agata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Retinoids are biologically active derivatives of vitamin A modulating cell proliferation, differentiation, apoptosis and altering the immune response. They have been used for years in therapy of cutaneous T-cell lymphomas (CTCL) but the exact mechanism of retinoids’ action is unclear. It is based on the presence of specific receptors’ families, mediating the biological effects of retinoids on the tumor cells: retinoic acid receptor (RAR) and retinoic X receptor (RXR). Orally administrated bexarotene, the first synthetic selective RXR retinoid, was revealed to be active against the cutaneous manifestation of CTCL. The toxicity profile caused by bexarotene seems to be more limited to laboratory values and better tolerated than classical retinoids, but generally associated with more severe grades of toxicity. Both selective retinoic acid receptor- and retinoic X receptor-mediated retinoids have modest objective response rates and, therefore, most likely will have limited impact as monotherapeutic agents. However, the immunomodulatory effects of RAR and RXR retinoids provide a rational basis for using retinoids in combination with other biologic immune response modifiers, phototherapy and radiotherapy. The authors reviewed the literature on the results of the use of retinoids and rexinoids in patients with mycosis fungoides and Sézary syndrome.